2023
DOI: 10.1021/acsnano.2c12190
|View full text |Cite
|
Sign up to set email alerts
|

Biomimetic Nanoparticle-Mediated Target Delivery of Hypoxia-Responsive Plasmid of Angiotensin-Converting Enzyme 2 to Reverse Hypoxic Pulmonary Hypertension

Abstract: Hypoxic pulmonary hypertension (HPH) is characterized by pulmonary vascular sustained constriction and progressive remodeling, which are initiated by hypoxia then with hypoxia-induced additive factors including pulmonary vascular endothelium injury, intrapulmonary angiotension system imbalance, and inflammation. Now HPH is still an intractable disease lacking effective treatments. Gene therapy has a massive potential for HPH but is hindered by a lack of efficient targeted delivery and hypoxia-responsive regula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…This incites an intracellular signaling cascade, leading to the interruption of TJs and reorganization of the actin cytoskeleton, consequently enabling CM@AIE NPs to traverse the BBB silently (Figure B) . Aside from deploying membranes derived from a singular cell source such as red blood cell, platelet, immune cell, and cancer cell; hybrid cell membranes also offer a promising strategy . Employing a cancer cell-mitochondria hybrid membrane enables the targeted delivery of OXPHOS inhibitors within GBM, which has facilitated the treatment of GBM stem cell xenografts in mice (Table ).…”
Section: Nanodelivery Systems For Sniping Cscsmentioning
confidence: 99%
“…This incites an intracellular signaling cascade, leading to the interruption of TJs and reorganization of the actin cytoskeleton, consequently enabling CM@AIE NPs to traverse the BBB silently (Figure B) . Aside from deploying membranes derived from a singular cell source such as red blood cell, platelet, immune cell, and cancer cell; hybrid cell membranes also offer a promising strategy . Employing a cancer cell-mitochondria hybrid membrane enables the targeted delivery of OXPHOS inhibitors within GBM, which has facilitated the treatment of GBM stem cell xenografts in mice (Table ).…”
Section: Nanodelivery Systems For Sniping Cscsmentioning
confidence: 99%
“…Increasing knowledge in tumor biophysics and biochemistry, especially tumor microenvironments, has promoted the development of stimuli-responsive nanocarriers for precise and specific drug release [195][196][197][198][199][200]. Triggered by internal stimuli such as tumoral acid [201][202][203][204][205][206][207][208], redox [209][210][211][212][213][214][215][216][217][218][219][220][221][222][223][224][225], hypoxia [226][227][228][229][230][231], and enzymes [232][233][234][235][236][237][238][239], or external stimuli like near-infrared (NIR) light and ultrasound [240][241][242...…”
Section: Stimuli-responsive Nanomedicines For Cancer Immunotherapymentioning
confidence: 99%
“…Additionally, Yang et al recently demonstrated the effectiveness of tumor-specific PEGylated bilirubin nanoparticles loaded with drug dimers, which suppressed robust 4T1 breast cancer cells . Further, these drug nanocarriers can be classified based on the different triggering mechanisms such as magnetic-responsive, pH-responsive, light-responsive, enzyme-responsive, and hypoxia-responsive . Xu et al, encapsulated DOX in poly­(acrylic acid) stabilized with amorphous calcium carbonate nanoparticles for sustainable release of drug by sensing the acidic pHs environment zebrafish model for eradication of human hepatocarcinoma cell line (SMCC-7721).…”
Section: Introductionmentioning
confidence: 99%
“… 22 Further, these drug nanocarriers can be classified based on the different triggering mechanisms such as magnetic-responsive, 23 25 pH-responsive, 26 light-responsive, 27 enzyme-responsive, 28 and hypoxia-responsive. 29 Xu et al, 30 encapsulated DOX in poly(acrylic acid) stabilized with amorphous calcium carbonate nanoparticles for sustainable release of drug by sensing the acidic pHs environment zebrafish model for eradication of human hepatocarcinoma cell line (SMCC-7721). However, these pH-sensitive drug release systems do not provide precise control over drug release rates and can lead to unpredictable release kinetics.…”
Section: Introductionmentioning
confidence: 99%